Conflict of Interest in Global, Public and Corporate Governance. - Handschin, Lukas (Cambridge University Press, 2012)
Conflict of interest occurs at all levels of governance, ranging from local to global, both in the public and the corporate and financial spheres. There is increasing awareness that conflicts of interest may distort decision-making processes and generate inappropriate outcomes, thereby undermining the functioning of public institutions and markets. However, the current worldwide trend towards regulation, which seeks to forestall, prevent and manage conflicts of interest, has its price. Drawbacks may include the stifling of decision-making processes, the loss of expertise among decision-makers and a vicious circle of distrust. This interdisciplinary and international book addresses specific situations of conflict of interest in different spheres of governance, particularly in global, public and corporate governance.